The Gardens of Singapore : Enthusing and Educating the Public in the World of Plants - Lindsay, Stuart; Middleton, David (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2018)
Singapore has several public gardens of which two, Singapore Botanic Gardens and Gardens by the Bay, are of particular national and international renown. These two gardens have contrasting but complementary ways of enthusing and educating the public about plants and of gaining their support for horticultural excellence, botanical research and conservation. Founded in 1859, Singapore Botanic Gardens is an old and established garden with a long history of horticultural and botanical research, plant exploration and conservation. It became a UNESCO World Heritage Site in July 2015, the world’s first tropical botanic garden to receive this accolade. Gardens by the Bay opened in 2012 and its focus is on large-scale displays in spectacular settings, thereby attracting huge numbers of visitors since its opening. In their contrasting ways, both gardens enthuse and educate the public about plants and the natural world. This work lays the foundations for public advocacy of conservation efforts in Singapore, resulting in a very high level of public support for greening efforts and the protection of natural areas in land-scarce Singapore.